Evaluation of academic performance with project-based learning in times of pandemic and post pandemic. (LACCEI, 2024)
During the pandemic period and the forced implementation of online education, there arose an imminent need to renew teaching practices. Virtuality challenged the methodologies used and the learning evaluation systems, since it was not enough to simply transfer the face-to-face class to a synchronous remote system. Aware of this limitation, a proposal for renewal emerged in Mathematics courses for the Engineering career, focused on active and student-centered learning. For the purpose of analysis, we have collected data from 2020 to date considering different groups of students who have taken the Integral Calculus course. The results show that as the years go by, student burnout has increased due to maintaining online classes with negative effects on the learning process. However, the learning methodologies are widely valued for providing skills despite the negative aspects of virtuality.